High-Frame Rate Vector Flow Imaging Technique: Initial Application in Evaluating the Hemodynamic Changes of Carotid Stenosis Caused by Atherosclerosis - Qiu, Yijie; Dong, Yi; Mao, Feng; Zhang, Qi; Yang, Daohui; Chen, Kailing; Shi, Shuainan; Zuo, Dan; Tian, Xiaofan; Yu, Lingyun; Wang, Wen-Ping (Frontiers in Cardiovascular Medicine, 2021)
Objective: To investigate the value of high-frame rate vector flow imaging technique (V Flow) in evaluating the hemodynamic changes of carotid stenosis caused by atherosclerotic plaques. Methods & Materials: In this prospective study, patients with stenosis rate (diameter) ≥ 30 % caused by carotid atherosclerotic plaques were included. Degrees of carotid stenosis were graded according to North American Symptomatic Carotid Endarterectomy Trial (NASCET) criteria: moderate (30 – 69 %) or severe (70 – 99 %). Mindray Resona 7s ultrasound machine with a linear array transducer (3-11 MHz) was used for ultrasound examinations. The mean WSS value of carotid arteries was measured at the proximal, narrowest region and distal of carotid stenosis. The mean WSS value were correlated with peak systolic velocity (PSV) measured by color Doppler flow imaging and stenosis degree detected by digital subtraction angiography (DSA). The vector arrows and flow streamline detected by V Flow dynamic imaging were analyzed. Imaging findings of DSA in carotid arteries were used as the gold standard. Results: Finally, 51 patients were included. V Flow measurements were performed successfully in 17 (100%) patients with moderate grade stenosis and in 30 (88.2%) patients with severe grade stenosis. Dynamic V Flow imaging showed yellow or red vectors at the stenotic segment, indicating fast speed blood flow. Changes of streamlines were detected in the stenotic segment. The mean WSS value measured at the narrowest region of the carotid artery had a moderately positive correlation with stenosis degree (r = 0.58, P < 0.05) and PSV value (r = 0.54, P < 0.05) respectively. Significant difference was detected in mean WSS value at the narrowest region of the carotid artery between severe carotid stenosis (1.47 ± 0.97 Pa) and moderate carotid stenosis (0.96 ± 0.44 Pa) (P < 0.05). Conclusion: The hemodynamic changes detected by V Flow of the carotid stenosis might be a potential non-invasive imaging tool for assessing the degree of carotid stenosis. Key Words Vector flow imaging (V Flow); wall shear stress (WSS); hemodynamic change; carotid atherosclerotic plaques; stenosis